Formation of endoperoxides from Mn(III)-induced reaction of 1,1-diarylethene, diketene and ethanol - Ha, Nguyen Van; Nishino, Hiroshi (Vietnam Journal of Chemistry, 2015)
Diketene reacted with manganese(III) acetate dihydrate in the presence of ethanol as a nucleophile to give a mixture of nonconjugated manganese(III) enolate A and conjugated manganese(III) enolate B. Major 1,2-dioxan-3-ol products 2 and 4 were formed by the oxidation of unstable nonconjugated manganese(III) enolate A. The proportions of 2 and 4 depended on the amount of diketene used. 1,2-Dioxan-3-ol 3 derived from the conjugated manganese(III) enolate B was also obtained as a minor product. The reaction pathways are briefly discussed.